EFFECTS of PREFERRED and NONPREFERRED MUSIC on CONTINUOUS CYCLING EXERCISE PERFORMANCE - Nakamura, Priscila M. [UNESP]; Pereira, Gleber; Papini, Camila B. [UNESP]; Nakamura, Fabio Y.; Kokubun, Eduardo [UNESP] (Ammons Scientific, Ltd, 2010)
The aim of this study was to investigate the effects of preferred and nonpreferred music on exercise distance, Heart Rate (HR), and Rating of Perceived Exertion (RPE) during continuous cycling exercise performed at high intensity Fifteen participants performed five test sessions During two sessions, they cycled with fixed workload on ergometer to determine the Critical Power (Cl') intensity Then, they performed three more sessions cycling at CP intensity listening to Preferred Music, listening to Nonpreferred Music, and No Music The HR responses in the exercise sessions did not differ among all conditions However, the RPE was higher for Nonpreferred Music than in the other conditions The performance under Preferred Music (9 8 +/- 4 6km) was greater than under Nonpreferred Music (7 1 +/- 3 5km) conditions Therefore, listening to Preferred Music during continuous cycling exercise at high intensity can Increase the exercise distance, and individuals listening to Nonpreferred Music can perceive more discomfort caused by the exercise